Analisis Perceived Ease of Use, Perceived Security, Perceived Risk pada Pengguna Potensial Paylater di Kalangan Gen Z - Gita Safitri; Usep Suhud; Meta Bara Berutu (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyse the influence of perceived ease of use, perceived security, and perceived risk on user trust and intention to use a paylater service among Generation Z in Jakarta. A quantitative approach was employed using purposive sampling, and the data were analysed through Structural Equation Modelling (SEM) with the AMOS software. Primary data were collected through an online Likert-scale questionnaire with a sample of 250 respondents. The research results show that perceived ease of use has a significant positive effect on both user trust and intention to use. Furthermore, perceived security has a significant positive effect on user trust. On the other hand, perceived security has a significant effect but with a negative direction, which is inconsistent with the initial hypothesis regarding intention to use. Meanwhile, perceived risk also proves to have a significant effect but with a positive direction, contrary to the initial hypothesis regarding user trust. However, perceived risk does not show a significant effect on intention to use. Additionally, user trust also demonstrates a significant positive effect on intention to use.